Development of Organizing for Learning to Develop Critical Reading Skill In the Thai Language Learning Strand for Grade 10 Students - Pinitphon , Chuleeporn (Journal for Developing the Social and Community, 2023)
Abstract This research aimed to develop of organizing for learning to develop critical reading skill In the Thai Language Learning Strand for grade 10 Students. The research employed the research and development methodology; it comprised 4 steps: 1) the study of baseline data for development of the model of organizing for learning, 2) the design and development of the model of organizing for learning, 3) the tryout of the model of organizing for learning, and 4) confirmation on the effectiveness of the implementation of the model of organizing for learning. The research design was of the one group pretest posttest design. The experimental group consisted of 38 grade 10 students of Sarakhampittayakhom School in the first semester of the academic year 2020, obtained through cluster random sampling. The research instruments were: 1) the CHULEE MODEL of organizing for learning, 2) the handbook of the model, 3) plans of organizing for learning, 4) a critical reading ability test, 5) a questionnaire inquiring students’ satisfaction with the model of organizing for learning. The analysis of data employed the mean, standard deviation, and t-test (dependent samples) for hypothesis testing. The results were as follows: 1) The state of problems of learning and developing critical reading skill, according to the students’ opinion, on the whole, was at a high level, while for the teachers in the Thai Language Learning Strand, on the whole, the problem was at a moderate level. Also, the need for development of the model of organizing for learning of the students, on the whole, was at a high level; 2) The CHULEE MODEL of organizing for learning to develop critical reading skill In the Thai Language Learning Strand for grade 10 Students had 6 steps of organizing learning activities. Step 1 C (Creative Interest): creating creative interest; Step 2 H (Habit Sufficiency): creating the habit of sufficiency; Step 3 U (Understanding): presenting knowledge and understanding; Step 4 L (Like to Learn): studying with pleasure; Step 5 E (Evaluation): evaluating; and Step 6 E (Exchange of Idea): exchanging ideas and finding conclusions for more learning; 3) The implementation of the CHULEE MODEL of organizing for learning to develop critical reading skill for grade 10 Students of Sarakhampittayakhom School yielded the model efficiency of 84.99/82.59 and the post-learning critical reading skill was higher than the pre-learning, with statistical significance at the level of .01. Moreover, the students’ satisfaction was at a high level, and 4) The effectiveness of the model was confirmed by extending the use of the model to the extended group and it was found that the average post-learning critical reading score of the extended group was higher than the pre-learning, with statistical significance at the level of .01. The students in the extended group had their satisfaction with the CHULEE MODEL of organizing for learning at a highest level.